Tutorial: Background and Guidance for Using the ANSI/IES TM-30 Method for Evaluating Light Source Color Rendition. Issue 2 (3rd April 2022) - Royer, Michael P.
ABSTRACT: This tutorial article provides a comprehensive overview of the development and use of ANSI/IES TM-30-20, an American National Standard method for evaluating light source color rendition that is published by the Illuminating Engineering Society. Five years since its initial publication, TM-30 is increasingly used by lighting producers, specifiers, and researchers due to its superior accuracy and the expanded scope of provided information compared to predecessor tools for assessing color rendition. Making the most of these improvements requires people who use the method to be more knowledgeable and intentional, and this tutorial consolidates a range of information to assist with best practices. The article, arranged as a series of questions, includes information about the development of the standard, color rendering fundamentals, TM-30 measures and their meaning, TM-30 calculation details, and application of TM-30. The document does not provide instructions for performing TM-30 calculations, which is the purpose of the ANSI/IES TM-30-20 standard, which is freely available.